Efektivitas Pemberian Beberapa Jenis Herbisida terhadap Pertumbuhan Gulma dan Hasil Padi Sawah dengan Sistem Tanam Tabur Benih Langsung Tanpa Olah Tanah (TABELATOT) - I KADEK ANGGA ARIMBAWA; I KETUT ARSA WIJAYA; IDA AYU MAYUN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Effectiveness of Giving Some Herbicides on Weed Growth and Yield of Rice Plants with Direct Seed Sowing System without Ground (TABELATOT) One of the obstacles in rice cultivation is the presence of weeds. Weeds are plants that humans does not want in the located that can reduce agricultural yields. Weed control techniques in rice plants can be done by using herbicides. This study aims to determine the types of weeds that grow in rice cultivation with the tabelatot system for each type of herbicide used, to determine the effectiveness of each type of herbicide used on weed growth and lowland rice yield in the tabelatot system, to determine the type of herbicide. which one can increase the growth and yield of rice in a tabelatot planting system. This study used a randomized block design (RBD) with 4 treatments, namely control, logran herbicide, metafuron herbicide and benfuron herbicide. This treatment repeat six times. Based on the statistical results, it was found that the types of weeds that grew in rice cultivation were 2 (two) from grass groups, namely Echinochloa crusgalli (L.) Beauv, and Cynodon dactylon, 1 (one) from the nut group namely Cyperus difformis L, and 4 ( four) from broadleaf groups, among others, Monochria vaginalis (Burm.f.), Ludwigia octovalvis, Spenochlea zeylanica, and Limnocharis flava. The results showed that the herbicide treatment logran, metafuron and benfuron could reduce the weight of wet weeds m-2 at the age of 42 hss, 0.90 kg and 0.92 kg, respectively or decreased by 86%, 57% and 56% compared to the control, namely 2.13 kg and reduced the weight of oven dry weeds as much as 0.01 kg, 0.09 kg and 0.09 kg, respectively or decreased by 95%, 59%, and 59% compared with 0.22 kg without herbicide. he most effective herbicide in controlling weeds in the table cropping system is logran herbicide seen from the parameters of oven dry grain weight ha-1 (ton), the treatment of logran herbicides, metafuron and benfuron can produce weight of 5.31 tons, 5.28 tons respectively. and 5.25 tons or increased significantly by 65%, 64% and 63% compared to the control, namely 3.23 tonnes, the high yield was due to the ability of logran herbicides to suppress weed growth so as to minimize competition between rice and weeds.